The Role Of The Indonesian National Police (POLRI) In Conducting Investigations According To The Criminal Justice System In Relation To Law No. 2 Of 2002 On The Indonesian National Police And Law No. 8 Of 1981 On The Criminal Procedure Code (KUHAP) - Kurniawatie, Eka (Sean Institute, 2025)
Investigation is a crucial stage in the criminal justice system aimed at uncovering and collecting evidence to determine whether or not a criminal act has occurred. In this context, the Indonesian National Police (POLRI) plays a key role as investigators, as stipulated in Law No. 2 of 2002 on the Indonesian National Police and Law No. 8 of 1981 on the Criminal Procedure Code (KUHAP). This study aims to analyze the role of POLRI in conducting investigations and its relationship with the protection of suspects' rights in accordance with the principles of criminal procedural law. The findings indicate that POLRI has broad authority in investigations, including arresting, detaining, searching, and confiscating evidence. However, these investigative activities must be carried out professionally, transparently, and accountably to avoid abuse of power. Additionally, the relationship between investigative practices and the protection of suspects' rights is a critical issue in ensuring justice. The rights of suspects, such as the presumption of innocence, the right to legal assistance, and humane treatment, must be safeguarded throughout the investigative process. This study recommends enhancing the competence of investigators through continuous training, leveraging technology for transparency, strengthening internal oversight systems, and educating the public about suspects' rights. Consequently, POLRI is expected to effectively and with integrity fulfill its role as investigators while ensuring the protection of human rights within the criminal justice system.